Physalis angulata Linn. As a Potential Liver Antifibrotic Agent In Rats. - Bestari, Muhammad Begawan; Rohmawaty, Enny; Rosdianto, Aziiz Mardanarian; Usman, Hermin A.; Saragih, Winda A. M.; Zuhrotun, Ade; Hendriani, Rini; Wardhana, Yoga Windhu; Ekawardhani, Savira; Wiraswati, Hesti Lina; Agustanti, Nenny; Dewi, Sumartini; Wijaya, Muhammad Palar (The Indonesian Society for Digestive Endoscopy, 2023)
Background: No drug with a liver antifibrotic effect for treating non-alcoholic fatty liver disease (NAFLD) has been approved. Physalis angulata Linn., better known to Indonesian as ciplukan, has natural abilities in various metabolic and inflammatory diseases. This study aims to determine the effect of ethyl acetate fraction of P. angulata in the NAFLD rat model by examining alanine aminotransferase (ALT), cholesterol levels, and liver histopathological features, which are methods to evaluate the course of the disease and the potential antifibrotic effect.Method: This research is an in vivo study on male Wistar rats conducted at the Animal Laboratory, Faculty of Medicine, Universitas Padjadjaran, from September to November 2020. Rats were grouped randomly into seven groups of 5 each. The NAFLD models were created by giving a diet containing 20% margarine for four weeks. The intervention groups were given vitamin E, ethyl acetate fraction of P. angulata, and both combinations. The statistical analysis examined differences in each group based on their histopathological features, ALT, and cholesterol levels.Results: Histopathological results in the group given P. angulata at a dose of 0.32 mg resembled normal liver, and the ALT level was similar to vitamin E. The administration of P. angulata at 0.16 mg dose improved cholesterol levels.Conclusions: P. angulata ethyl acetate fraction at a dose of 0.32 mg improved the histopathological and serum ALT levels in the NAFLD rat model, which could be the basis for the mechanism of P. angulata's antifibrotic ability in NAFLD conditions.